Socialization of Environmental Impact Analysis (Amdal) on Manganese Mining Activities by PT. Elga Asta Media in Loloda Islands District, North Halmahera Regency - Saiful Hi. Soleman; Sudiar Kokoda (International Journal Of Community Service, 2022)
EIA socialization is the obligation of every mining business actor and is a very important part, in socializing AMDAL so that the public can know the activities carried out by the company. In order not to damage the environment and noise, for people who are active around the mining area. The Amdal socialization team conveyed the activities carried out so that the community could understand and know, so that in manganese mining activities carried out by PT. Elga Asta Media is located in Cera Village, Loloda District, North Halmahera Regency, North Maluku Province. Activities in the socialization of EIA were carried out in Cera Village with methods that were in accordance with the environmental conditions of the community. Conducted activities at the Cera Village office, Loloda Kepualauan Subdistrict, which was attended by the Loloda Kepulauan Camat, Head of Des, Village Apparatus, and the Community. Conducting socialization and interactive question and answer with the local community, the socialization of amdal was facilitated by the company and the sub-district government and village government. Socialization on mining activities based on an agreement between the company and the owner of the plant growing using the compensation method in accordance with applicable regulations and community agreements. Community service activities in the socialization of AMDAL can have a positive/significant impact on mining businesses and communities in the mining area, especially Cera, Dama, Dowonggila, and Salube Villages located in Loloda District, North Halmahera Regency, in order to commit to preserving the environment. properly and correctly.